Application of nuclear physics methods and NSC KIPT accelerators for investigation of solid composition - Skakun, N.A.; Svetashov, P.A. (Вопросы атомной науки и техники, 2003)
The results of application of nuclear physics methods and NSC KIPT accelerators in the fields of investigation of metals and alloys, semiconductors, oxidic metals and magnetic materials are outline. The results and potentialities of these methods for determination of concentration and distribution of micro quantities of elements and isotopes, investigation of features and properties of simplest defects are presented. The beams of (1–3) MeV hydrogen and helium ions were used. Element and isotope identification was realized by means of Rutherford backscattering, resonance nuclear reactions and incident ions induced X – ray radiation.